The resurrection of the pontoniine genus Urocaris Stimpson, 1860, (Crustacea: Decapoda: Palaemonidae) - Bruce, A. J. (Zootaxa, 2007)
The genus Urocaris Stimpson, 1860, has been re-assessed and separated from the genus Periclimenes Costa, 1844.